Giant Tarsal Keratinous Cyst Mimicking Chalazion - Melis Palamar Onay; Ayşe Yağcı; Taner Akalın (Türk Oftalmoloji Dergisi, 2013)
Reports on keratinous cysts involving the tarsal plate are very rare. Herein, we present a 69-year-old male patient with a giant tarsal keratinous cyst of the right upper eyelid who was misdiagnosed as chalazion of the eyelid. Interventional case report with cytopathologic correlation. Due to recurrence after the surgery for presumed chalazion, the patient was referred to our clinic for tumor evaluation. In the second surgery, which was performed in our clinic, the lesion was found to have a fine capsule and was totally excised. Histopathologic examination revealed keratinous cyst of the tarsal plate. Keratinous cyst must be considered in the differential diagnosis of tarsal plate lesions, as the curettage of the keratinous cyst might result in multiple recurrences. (Turk J Ophthalmol 2013; 43: 138-9)